Estimation and Determinants of Chinese Banks' Total Factor Efficiency: A New Vision Based on Unbalanced Development of Chinese Banks and Their Overall Risk - Shiyi Chen; Wolfgang Karl Härdle; Li Wang (Humboldt-Universität zu Berlin, International Research Training Group 1792 "High Dimensional Nonstationary Time Series", 2020)
The paper estimates banks' total factor efficiency (TFE) as well as TFE of each production factor by incorporating banks' overall risk endogenously into bank's production process as undesirable by-product in a Global-SMB Model. Our results show that, compared with a model incorporated with banks' overall risk, a model considering only on-balance-sheet risk may over-estimate the integrated TFE (TFIE) and under-estimate TFE volatility. Significant heterogeneities of bank TFIE and TFE of each production factor exist among banks of different types and regions, as a result of still prominent unbalanced development of Chinese commercial banks. Based on the estimated TFIE, the paper further investigates the determinants of bank efficiency, and finds that shadow banking, bank size, NPL ratio, loan to deposit ratio, fiscal surplus to GDP ratio and banking sector concentration are significant determinants of bank efficiency. Besides, a model with risk-weighted assets as undesirable outputs can better capture the impact of shadow banking involvement.
Keywords: C00; 330; Nonparametric Methods; Commercial Banks; Shadow Bank; Financial Risk